TECHNO-ECONOMICS REPLACEMENT MODEL OF PAINTING ROBOTS IN AUTOMOTIVE MANUFACTURING PLANT - FUDZIN, AHMAD FAUZI (2017)
The robots operated in an automotive assembly plant are a large portion of investment which contributes to the automation level of the manufacturing assembly line. Failures do occur and affect the operating efficiency of the robots, in term of maintenance and replacement cost. Timely replacement could reduce the downtime, which might result in significant savings for the company. The objective of this study is to develop a techno-economics replacement model for robots at the painting line of an automotive assembly plant in order to avoid major downtime due to unplanned failure. The methodology adopted based on indenture levels and mean times between failures (MTBF) were used as a basis for technical assessment. The analysis of indenture levels of plant and equipment for the automotive industry and maintenance levels was based on the actual plant and equipment layout. It was incorporated with the probability failure analysis, failure rate, mean time to repair (MTTR) and MTBF analysis. For the economics assessment, marginal cost (MC) and equivalent uniform annual cost (EUAC) were used. The replacement analysis decision map rule‘s was adopted to determine the robot with MC of defender is less than minimum EUAC of challenger will be kept in service for one more year. As a result of technical assessment as a case study, it was concluded that the third robot of top coat work cell as a candidate for replacement. The highest percentage of component failures due to servo motor faulty was mainly coming from this robot. It also had the highest number of failure and highest failure rate. The critical component analysis shows that the total investment of upgraded robot was carried out at year 11. Consequently, as the economics assessment, the analysis was started with the modified tabulation of MC for defender and EUAC for challenger. The result shows the MC of defender is less than minimum EUAC of challenger in the year 12; hence the third robot of work cell top coat will be used for one more year. Vice versa, in year 13 the MC of defender is higher than the minimum EUAC of challenger, thus replacement was proposed by end of year 13. Result indicates that the techno-economics replacement model able to assist the management of industry to assess the performance of equipment, machineries and robotic system and finally making a decision.